Genome-wide RNAseq study of the molecular mechanisms underlying microglia activation in response to pathological tau perturbation in the rTg4510 tau transgenic animal model - Wang, Hong; Li, Yupeng; Ryder, John W.; Hole, Justin T.; Ebert, Philip J.; Airey, David C.; Qian, Hui-Rong; Logsdon, Benjamin; Fisher, Alice; Ahmed, Zeshan; Murray, Tracey K.; Cavallini, Annalisa; et al. (Molecular neurodegeneration, 2018)
Activation of microglia, the resident immune cells of the central nervous system, is a prominent pathological hallmark of Alzheimer's disease (AD). However, the gene expression changes underlying microglia activation in response to tau pathology remain elusive. Furthermore, it is not clear how murine gene expression changes relate to human gene expression networks. Microglia cells were isolated from rTg4510 tau transgenic mice and gene expression was profiled using RNA sequencing. Four age groups of mice (2-, 4-, 6-, and 8-months) were analyzed to capture longitudinal gene expression changes that correspond to varying levels of pathology, from minimal tau accumulation to massive neuronal loss. Statistical and system biology approaches were used to analyze the genes and pathways that underlie microglia activation. Differentially expressed genes were compared to human brain co-expression networks. Statistical analysis of RNAseq data indicated that more than 4000 genes were differentially expressed in rTg4510 microglia compared to wild type microglia, with the majority of gene expression changes occurring between 2- and 4-months of age. These genes belong to four major clusters based on their temporal expression pattern. Genes involved in innate immunity were continuously up-regulated, whereas genes involved in the glutamatergic synapse were down-regulated. Up-regulated innate inflammatory pathways included NF-κB signaling, cytokine-cytokine receptor interaction, lysosome, oxidative phosphorylation, and phagosome. NF-κB and cytokine signaling were among the earliest pathways activated, likely driven by the RELA, STAT1 and STAT6 transcription factors. The expression of many AD associated genes such as APOE and TREM2 was also altered in rTg4510 microglia cells. Differentially expressed genes in rTg4510 microglia were enriched in human neurodegenerative disease associated pathways, including Alzheimer's, Parkinson's, and Huntington's diseases, and highly overlapped with the microglia and endothelial modules of human brain transcriptional co-expression networks. This study revealed temporal transcriptome alterations in microglia cells in response to pathological tau perturbation and provides insight into the molecular changes underlying microglia activation during tau mediated neurodegeneration.